2005
DOI: 10.1088/1741-2560/2/4/008
|View full text |Cite
|
Sign up to set email alerts
|

Steady-state visual evoked potential (SSVEP)-based communication: impact of harmonic frequency components

Abstract: Brain-computer interfaces (BCIs) can be realized on the basis of steady-state evoked potentials (SSEPs). These types of brain signals resulting from repetitive stimulation have the same fundamental frequency as the stimulation but also include higher harmonics. This study investigated how the classification accuracy of a 4-class BCI system can be improved by incorporating visually evoked harmonic oscillations. The current study revealed that the use of three SSVEP harmonics yielded a significantly higher class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
257
2
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 463 publications
(271 citation statements)
references
References 19 publications
6
257
2
6
Order By: Relevance
“…Figure 5 shows that the same frequencies that other subjects might use for control, 10 or 12 Hz, would not have allowed this subject to control a BCI. While other BCI studies have also reported that subjects may show stronger activity over the first, second, or even third harmonic (Gao et al, 2003;Müller-Putz et al, 2005), it is unclear whether this difference occurs due to natural variation among subjects, display and task parameters, different attentional strategies, or other factors.…”
Section: : Inter-subject Differences and Implications For Bcismentioning
confidence: 95%
See 2 more Smart Citations
“…Figure 5 shows that the same frequencies that other subjects might use for control, 10 or 12 Hz, would not have allowed this subject to control a BCI. While other BCI studies have also reported that subjects may show stronger activity over the first, second, or even third harmonic (Gao et al, 2003;Müller-Putz et al, 2005), it is unclear whether this difference occurs due to natural variation among subjects, display and task parameters, different attentional strategies, or other factors.…”
Section: : Inter-subject Differences and Implications For Bcismentioning
confidence: 95%
“…They can exhibit good information throughput relative to other BCIs (Sutter, 1992;Cheng et al, 2002;Gao et al, 2003;Müller-Putz et al, 2005). They can operate in challenging environments with uncontrolled distraction and electrical noise (Cheng et al, 2002;Wang et al, 2004;Trejo et al, 2006) and hence could work well in homes or hospital settings.…”
Section: : Future Directions With Ssvep Bcismentioning
confidence: 99%
See 1 more Smart Citation
“…Current BCIs relying on VEPs depend on gaze control [16,17] and thus fall into the category of dependent BCIs [1]. Therefore, these BCIs are not applicable to those whose severe disabilities extend to impaired or nonexistent ocular motor control, such as LIS patients in which (i) eye movements may be inconsistent, very small and easily exhausted in the acute stage and (ii) deteriorated or nonexistent oculomotor control could be observed in the chronic stage.…”
Section: Introductionmentioning
confidence: 99%
“…Ces avantages rendent la méthode particulièrement appropriée pour détecter la capacité de réponse à une commande au chevet de patients cérébrolésés, ces derniers présentant fré-quemment des mouvements involontaires (à l'origine de nombreux artefacts de mouvement) et pouvant difficilement s'entraîner durant plusieurs jours en raison de leur fatigabilité et des fluctuations de leur vigilance. Toutefois, les SSVEP-BCI dépendent généralement des canaux standard de communication que sont les nerfs périphériques et les muscles : le sujet doit disposer du contrôle de ses yeux afin de fixer directement du regard un des stimulus présentés dans son champ visuel en réponse à l'instruction (attention explicite, de l'anglais overt attention) [23]. Cette exigence ne pose aucun problème pour des sujets sains, mais limite fortement l'application de l'interface chez des patients dont le handicap moteur s'étend au contrôle oculaire (altéré ou inexistant).…”
Section: Vers Un Paradigme Visuel Indépendantunclassified